O artigo científico como mercadoria acadêmica - Castro, Maria das Graças Monteiro (2018)
This research study is based on the premise that the research article has become one of the most privileged means of constructing and communicating the knowledge produced in universities, and even the only yardstick for measuring intellectual and scientific work in various fields of expertise. Thus, it aims to address the political, economic, and cultural determinations underlying the centrality of the research article as the most valued product of the Brazilian public university; its implications for scholars’ working conditions; the effects of research and intellectual production for the academic career. This study is grounded on the neoliberal paradigm within the context of globalisation, a paradigm which has determined economic changes in Brazil since the 1990s and imposed a productivist logic as a way to regulate global reorganisation of the economy and of labour. Work productivity is viewed as central to this form of capital accumulation, transforming the general conditions of production and of labour. The implementation of a neoliberal policy in Brazil in the last two decades has promoted a higher education reform and a new configuration of public universities. Discussing the role of universities in a neoliberal world from a Marxist perspective reveals, therefore, the process of neoliberalisation in public universities and the significant changes brought about to the work of scholars. By addressing the nature of academic work and its productivist logic, this study examines the leading role of the research article within Brazilian scientific production and the homogenisation of forms and values assigned by the metrication of productivity assessment. It offers a discussion of assessment notions guiding current political interventions, the role of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes) in implementing an assessment policy that acts as an instrument of control and regulation, and the research article as a form of academic merchandise.